PERBEDAAN KADAR HEMOGLOBIN (HB) SEGERA DIPERIKSA DAN DITUNDA SELAMA 6 JAM PADA SUHU KULKAS 4-8°C MENGGUNAKAN HEMATOLOGY ANALYZER - Indah Sari; Aisah Oktavia; Aristoteles, Aristoteles (IKesT Muhammadiyah Palembang, 2024)
Background: Hematology examination is an examination carried out to determine the condition of the blood and its components in the blood. Blood consists of erythrocytes, leukocytes, platelets, and a yellowish liquid called plasma. Hemoglobin is a tetrameric protein of erythrocytes that binds to non-protein molecules, namely iron porphyrin compounds called heme. Hemoglobin has an important role in the transportation system in the human body, the main thing is to transport oxygen to all tissues and the second is to move carbon dioxide from peripheral tissues to respiratory organs. Hemoglobin levels can be measured using an automatic cell counter (hematology analyzer) which directly measures hemoglobin levels. Purpose: To find out the difference between immediate and delayed blood tests for 6 hours at 4-8 to hemoglobin levels using Hematology Analyzery. Research Methods: The type of research conducted in this research is cross sectional. samples used were 30 samples in the UPTD Puskesmas tebing tinggi. The hemoglobin level was checked using a Hematology analyzer. Results: in the study, it was found that hemoglobin levels were immediately checked with an average of 13.51 gr/dL while hemoglobin levels were delayed for 6 hours at 4-8 obtained an average hemoglobin level of 11.33 gr/dL Conclusion: on examination of hemoglobin immediately and delayed 6 hours at a temperature of 4-8 there was a decrease of 2.18 gr/dl.